DIGITAL RIGHT MANAGEMENTS (TEKNOLOGI PENGAMAN) DALAM PERLINDUNGAN TERHADAP HAK CIPTA DI ERA DIGITAL - Irawati, Irawati (Diponegoro Private Law Review, 2019)
ABSTRACT  The digital age has driven all changes in people's behavior in every sector of life. The development of technology has given birth to a new phenomenon in the field of Copyright protection which is one of the scope of Intellectual Property (KI). in copyright protection, internet technology experts and Copyright seek to create a variety of technologies that are expected to provide Copyright protection on the Internet, which is called Security Technology. One of the standard terms of Safety Technology is known as Digital Right Management (DRMs) The existence of Safety Technology (DRMs) has been accommodated in the Law No.28 of 2014. Safety Technology is software, components or other tools that can be used by Copyright owners to protect their works. Security technology can be an encryption from Software, a password, and an access code. Security Technology can guarantee exclusive rights contained in Copyright for creators